ealing with difficult people 24 lessons for bringing out the best in everyone - Brinkman, Rick; Kirschner, Rick (McGraw-Hill professional education, 2003)
THE MCGRAW-HILL PROFESSIONAL EDUCATION SERIES These quick reads, based on McGraw-Hill bestsellers, are designed to meet the needs of busy people. Titles in the series focus on each book's main themes and action ideas, reduced to a manageable page count for on-the-go readers. Specific strategies for understanding the 10 types of problem people and influencing them to adopt positive behaviors